The DRIL procedure for arteriovenous access ischemic steal: a controversial approach. Issue 1 (January 2017) - Davidson, Ingemar; Beathard, Gerald; Gallieni, Maurizio; Ross, John
The DRIL procedure first described in 1988 has long been considered the preferred treatment for arteriovenous access ischemic steal (AVAIS). At the time it was a brilliant concept and breakthrough. In the last decade, the DRIL procedure has become less used. With the increasing age of the dialysis population, patients developing AVAIS are more likely to be elderly with advanced peripheral arterial disease, making the distal revascularization anastomosis difficult and risky if not impossible to perform. In addition, the distal ligation of the main artery to the arm is something most surgeons are reluctant to do. The occlusion of the arterial bypass over time is not uncommon with recurrence of hand ischemia. The multistep DRIL procedure requires general anesthesia and the need to harvest the saphenous vein for the bypass, add to the surgical risk in patients with multiple co-morbidities. For these reasons, some surgeons prefer to do only the DR (distal re-vascularization) portion of the procedure omitting the IL (interval ligation). Increasing the bypass distance from the original anastomosis, makes this modification similar to the less invasive proximal arterial inflow (PAI) procedure. Conclusions: Because of changes in the patient population clinical presentation, most notably forearm atherosclerosis and with new technologies, this editorial addresses the current validity of the DRIL procedure as a safe option in treating AVAIS.